2009
DOI: 10.1590/s0100-67622009000600007
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of five forest species to Coptotermes gestroi

Abstract: - SUSCEPTIBILITY OF FIVE FOREST SPECIES TO Coptotermes gestroi1 RESUMO -Os térmitas são bem conhecidos por sua capacidade de danificar madeira e vários tipos de produtos derivados. O estudo foi realizado no município de Seropédica, RJ, com o objetivo de avaliar a susceptibilidade da madeira de cinco essências florestais à ação do cupim subterrâneo asiático, Coptotermes gestroi. Como corpos-de-prova foram utilizados estacas de madeiras das seguintes essências florestais: pinho (Pinus sp.) (Pinaceae), castanheir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Based on the results of the laboratory tests, 10 cm pieces would be the most adequate size for this because they attracted the greatest mass recruitment. However, more studies are needed to support these hypotheses, since in addition to foraging behavior inherent to the species, other factors might interfere with termite foraging, such as edaphoclimatic conditions, presence of other food sources and predators, soil structure and humidity, and level of soil disturbance (Hu & Appel, 2004;Souza et al, 2009;Santos et al, 2010;Dow AgroSciences, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the laboratory tests, 10 cm pieces would be the most adequate size for this because they attracted the greatest mass recruitment. However, more studies are needed to support these hypotheses, since in addition to foraging behavior inherent to the species, other factors might interfere with termite foraging, such as edaphoclimatic conditions, presence of other food sources and predators, soil structure and humidity, and level of soil disturbance (Hu & Appel, 2004;Souza et al, 2009;Santos et al, 2010;Dow AgroSciences, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, given the long time since their construction (>200 years), the quality of the wood had deteriorated due to environmental factors. Basidiomycete fungi can change the wood’s physical–mechanical properties and reduce the durability of wooden materials [ 48 ] that are preferred by termites [ 22 ]. Fungal mycelium can trigger and accelerate termite activity and consequently increase the level of wood destruction [ 4 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The timber and construction industries are suspected to be the most effective media for the spread of C. gestroi in Indonesia. Even though wood preservation methodsagainst C. gestroi are well developed [ 21 , 22 ], economic loss caused by this species is increasing in Southeast Asia [ 21 ], and Coptotermes spp. are known to be serious pests, attacking buildings in China [ 23 ], Malaysia [ 24 ], and Indonesia [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Food preference tests showed that N and P are phagostimulants in the termite diet [11,31]. Properties such as hardness (density) and secondary compound contents can also be determinants of the choice and consumption of food items [32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%